Volunteerism as an alternative early warning system in supporting election supervision - Caroline Paskarina (Masyarakat, Kebudayaan dan Politik, 2018)
The quality of an election can be measured by the number of violations that can be solved to ensure the legitimisation of the election results. Violations in elections are still a problem since the amount tends to increase, which needs a long period of time to be solved. The enforcement of the regulations, such as the role of Bawaslu, is limited because it only serves as a ‘postman’ who forwards the violation cases to another law enforcement institution. The shifting of electoral supervision towards a more participatory approach has become an opportunity to develop an electoral supervision model that involves the community, especially in the prevention phase. This article describes the emergence of the idea of volunteerism in the context of the election, particularly in the election’s implementation monitoring and supporting the functions of Bawaslu. The article uses qualitative methods to analyse the various regulations in relation to monitoring and supervising the election, as well as various referral sources that contain voluntary practice information. The result of the study shows that an early detection system is an alternative method that can be developed, considering the voluntary spirit which is currently undergone an improvement. Therefore, it is necessary to build an early system in the prevention phase by conducting supervision on the implementation of the overall stages of the election and building public awareness to guard the integrity of the election results.